Comparative Analysis of Friction Coefficient Evolution in Hydroelectric Dam Penstocks: Theoretical vs. Numerical Methods (Global Journals of Research in Engineering, 2024)
The objective of this study was to investigate the evolution of the friction coefficient throughout a full penstock using two different approaches Two approaches were considered in order to assess their effectiveness in predicting head loss A theoretical approach that based on direct determination using the commonly used Colebrook-While formula A graphical approach that based on numerical modeling of the structure under study using Gambit 2 2 software For the theoretical approach the results show that whatever the other parameters set out in the Colebrook-White formula Reynolds number diameter and absolute roughness only absolute roughness has a visible impact on the result obtained For the numerical approach the results obtained show that the friction coefficient is neither identical on the same wall nor identical in the same portion Nor is it identical in the same section of the pipe as shown by the theoretical approach This shows that head loss in a section of pipe can change over time
Keywords: friction coefficient; penstock; hydroelectric dam; theoretical approach; numerical approach